KAJIAN LITERATUR: KESULITAN SISWA SEKOLAH DASAR DALAM MEMAHAMI SOAL CERITA MATEMATIKA - Delon Pratama; Melva Zainil; Inggria Kharisma; Annisa Olivia Memosa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Word problems in elementary school mathematics learning play an important role in developing students’ logical thinking, problem-solving skills, and mathematical literacy. However, in reality, many elementary school students still experience difficulties in understanding and solving mathematical word problems. These difficulties are not only related to arithmetic skills but also to the ability to understand the content of the problems, identify important information, and connect the problems into mathematical models. Therefore, this study aims to identify the types of difficulties experienced by elementary school students in understanding mathematical word problems, the factors influencing these difficulties, and the efforts that can be made to overcome them. The method used in this study is a literature review by analyzing various scientific sources such as journals, research articles, and books relevant to the topic. The analysis was conducted descriptively to obtain an overview of the common problems experienced by students in solving mathematical word problems. The results of the study indicate that students’ difficulties include low comprehension of the language used in the problems, inability to identify known and asked information, errors in transforming problems into mathematical operations, and weak calculation skills. The factors causing these difficulties come from both internal and external factors. Internal factors include low learning interest, reading ability, motivation, and students’ understanding of mathematical concepts. Meanwhile, external factors include less varied teaching methods, limited learning media, unsupportive learning environments, and lack of family assistance. Based on the findings, contextual, innovative, and student-centered learning approaches are needed to improve students’ ability to understand mathematical word problems optimally. Keywords: mathematical word problems, learning difficulties, elementary school, mathematical literacy, problem solving.